(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The introduction of the Goods and Services Tax (GST) in India on July 1, 2017, marked a significant shift in the country’s indirect tax system, aiming to simplify and harmonize the tax structure. This paper explores the challenges and opportunities faced by women entrepreneurs in the post-GST implementation phase. By analyzing secondary data sources, the study identifies key areas where GST has impacted women-led businesses, both positively and negatively. The findings highlight the complexities of GST compliance, access to technology, and financial literacy as significant challenges, while opportunities lie in the streamlined tax processes and potential market expansion. The study underscores the need for targeted support and policy interventions to empower women entrepreneurs in leveraging the benefits of GST.